Impact of Unqualified Housing on Childhood Pneumonia: A Spatial Study in Urban and Rural of Bojonegoro, Indonesia - Nur Lathifah Syakbanah; Salwa Nabilah; Muhammad Hanif; Marsha Savira Agatha Putri; Adisti Risma Putri Azzahra Arismaya; Eka Lailatun Nafisah; Yudied Agung Mirasa (Poltekkes Kemenkes Surabaya, 2025)
Unhealthy housing poses significant risks for children's respiratory health, such as pneumonia. Indoor and outdoor environmental factors can vary between urban and rural areas. Spatial vulnerability mapping is a potential tool for developing an early warning system for policymaking in pneumonia control. The purpose of this study was to determine the spatial vulnerability of unqualified housing factors among childhood pneumonia in both urban and rural areas of Bojonegoro, Indonesia. This study employed a cross-sectional design with spatial analysis to determine the correlation and distribution map of eight housing factors of childhood pneumonia in comparison between urban and rural areas. 60 mothers of under-five children as samples for interview and housing factors assessment. Six (54.5%) and four (28.6%) villages had high prevalence cases in urban and rural areas, respectively. Concentrated in the city center and home industries of Bojonegoro sub-district, then livestock and agriculture area of Sukosewu sub-district. Humidity in urban (P=0.03; PR=16.50) and rural (P=0.04; PR=12.60), lighting in urban (P=0.01; PR=23.00) and rural (P=0.04; PR=12.60), house occupancy density in urban and rural (P=0.04; PR=12.60), and ventilation area in rural (P=0.03; PR=25.00) were correlated to childhood pneumonia. Six urban and four rural villages exhibited a high prevalence of pneumonia cases. Unqualified humidity, lighting, house occupancy density, and ventilation area impact childhood pneumonia. It is recommended to improve natural or mechanical housing ventilation, adjust the total housing occupants, and update national healthy housing standards. The use of spatial analysis effectively identified housing-related risk factors for pneumonia, providing critical insights for developing targeted interventions in Bojonegoro.